An interview with David Henry: supportive oncology, anemia and cancer. (September 2015) - Henry, David H
David H Henry, MD, is a practicing hematologist/medical oncologist and Clinical Professor of Medicine at the Pennsylvania Hospital in Philadelphia (PA, USA), where he holds the title of Vice Chairman of the Department of Medicine. He is Editor in Chief of the Journal of Community and Supportive Oncology . For the past 25 years, he has had a special interest in supportive oncology and participated in clinical trials using growth factors to treat cancer-related anemia with or without intravenous iron, neutropenia, thrombocytopenia and bone metabolism due to bone metastases. He is also the Director of the HIV Malignancy Program and Director of the Austrian Medical Student Program at Pennsylvania Hospital.